Ground Settlement of Deeply Buried Two-Lane Tunnels with Large Cross-Sections Using Different Construction Methods - Yugang Han; Changming Wei; Mengyuan Cui; Hong Xie; Yangwang Ou; Hao Zhu; Taoying Liu (Applied Sciences, 2022)
To ensure the safety of excavations such as large section tunnels of the Guangxi Liubin Highway Tunnel Project, we implemented a simulation analysis of 3D tunnel models based on finite software for different construction methods. Different from the traditional simulation, this paper uses various construction methods to compare, study, and analyze the advantages and disadvantages of different excavation methods by combining them with the excavation. The feasibility of different construction methods was analyzed by studying the mechanical characteristics and settlement changes using the Cross Diaphragm (CRD), Center Diaphragm (CD), and full-section methods while building a large section tunnel. The arch perimeter deformation and surface settlement during the initial support and secondary lining proved that the CRD excavation method is the most favorable and causes the least damage to the stability of the surrounding rock. For the analysis of surface subsidence, the “V”-shaped surface subsidence curve excavated by the CRD method is the closest to the subsidence curve. However, we used the adjusted peak formula to fit the prediction formula for the surface settlement curve of the deep-buried two-lane tunnel with a large cross-section applicable to this project, which will provide an important reference for similar projects.